Sunflowers genotypes agronomics features in the second harvest in Muzambinho (MG) - Expedito Lense, Guilherme Henrique; Bócoli, Fernanda Almeida; Alves, Alberto Donizete (Revista Agrogeoambiental, 2020)
The sunflower (Helianthus annuus L.) is an oilseed crop with agronomic features that justify its tillage in the southeast of Brazil. The objective of this work was to evaluate the agronomic performance of sunflower genotypes tallaged in Muzambinho (MG) in the second harvest. It was adopted the randomized blocks design, with six genotypes (MULTISSOL, BRS G35, BRS G47, BRS G48, M734, and SYN 045) and four repetitions, totalizing 24 experimental plots with an area of 16.8 m2 on its plot. The plant population adopted was about 45000 plants ha-1. The obtained data were submitted to the analysis of variance and the Tukey test, by 5% of probability. There was variation in the agronomic performance of the genotypes to all evaluate parameters. The variety of MULTISSOL was the genotype that presented the larger precocity. The hybrid SYN 045 presented the longer cycle. The hybrid M734 is the genotype with a bigger weight of 1.000 achenes. The genotypes that provided the better yield of grains and oil were M734, SYN 045 and BRS G48. The biggest oil content in the achenes was observed in SYN 045 e BRS G48.